Effects of Different Roughages on Growth Performance, Nutrient Digestibility, Ruminal Fermentation, and Microbial Community in Weaned Holstein Calves - Li, Jichao; Lian, Hongxia; Zheng, Airong; Zhang, Jiangfan; Dai, Pengfei; Niu, Yan; Gao, Tengyun; Li, Ming; Zhang, Liyang; Fu, Tong (Frontiers in Veterinary Science, 2022)
The objective of this study was to assess the effects of feeding with different roughages on the growth performance, nutrient digestibility, ruminal fermentation and microbial community of weaned Holstein calves. Fifty-four Holstein calves (body weight (BW) = 77.50 ± 5.07 kg; age = 70 ± 2.54 d) were assigned to 1 of 3 treatment groups (n=18/group) that offered diets with different roughages: (1) peanut vine (PV), (2) oat hay (OH), or (3) an alfalfa hay + oat hay combination (alfalfa hay: oat hay =1:1, AO). Starter and roughage intakes were recorded daily, while BW and growth measurements were assessed at 15 d intervals. Apparent digestibility of nutrient was determined. Rumen fluid samples were collected and used to detect relevant indicators. The results showed that the final BW, average daily feed intake (ADFI) and average daily gain of the PV calves were significantly higher than those of the other groups (P < 0.05). The apparent digestibility of dry matter and organic matter of calves in PV group was significantly higher than that in OH group (P < 0.05). In addition, the propionate concentration significantly increased in the rumen fluids of calves in the PV group and AO group (P < 0.05). At the genus level, the abundances of Rikenellaceae_RC9_gut_group, Shuttleworthia and unclassified_o__Bacteroidales showed distinct responses to feed different roughages (P < 0.05). The relative abundance of Shuttleworthia was negatively correlated with rumen pH and acid detergent fiber digestibility (P < 0.05) and strongly positively correlated with propionate concentration (P < 0.01). Ruminococcus_1 was positively correlated with butyrate, ammonia nitrogen concentrations and neutral detergent fiber digestibility (P < 0.05). The relative abundances of Succiniclasticum and Prevotella_7 was negatively correlated with butyrate concentration (P < 0.05). In conclusion, the peanut vine used as roughage source could promote the growth performance, apparent digestibility of nutrient and rumen fermentation in weaned Holstein calves, which could be attributed to increase ADFI and change the rumen microflora. These results indicated that peanut vine could be used as a high-quality roughage in weaned calves.